High-risk and Long-term Opioid Prescribing to Military Spouses in the Millennium Cohort Family Study. Issue 9 (22nd July 2020) - McDonald, Douglas C; Radakrishnan, Sharmini; Sparks, Alicia C; Corry, Nida H; Carballo, Carlos E; Carlson, Kenneth; Stander, Valerie A
Abstract: Introduction: The use and misuse of opioids by active service members has been examined in several studies, but little is known about their spouses' opioid use. This study estimates the number of military spouses who received high-risk or long-term opioid prescriptions between 2010 and 2014, and addresses how the Military Health System can help prevent risky prescribing in order to improve military force readiness. Materials and Methods: This study used data from the Millennium Cohort Family Study, a nationwide survey of 9, 872 spouses of service members with 2 to 5 years of military service, augmented with information from the military's Pharmacy Data Transaction Service about prescriptions for controlled drugs dispensed to these service members' spouses. Our objectives were to estimate the prevalence of opioid prescribing indicative of long-term use (≥60 day supply or at least one extended-release opioid prescription in any 3-month period) and, separately, high-risk use (daily dosage of ≥90 morphine mg equivalent or total dosage of ≥8, 190 morphine mg equivalent, or prescriptions from more than three pharmacies, or concurrent prescriptions). For each of these dependent variables, we conducted bivariate analyses and multiple logistic regression models using information about spouses' physical health, sociodemographic characteristics, substance use behaviors, perceived social support, and stresses associated with military stress, among others. Informed consent, including consent to link survey responses to medical and personnel records, was obtained from all participants. The Naval Health Research Center's Institutional Review Board and the Office of Management and Budget approved the study. Results: Spouses were predominantly female (86%), had not served in the military themselves (79%), and were spouses of enlisted (91%) active duty (86%) service members. Almost half (47.6%) of spouses obtained at least one opioid prescription during the 2-year observation window, and 8.5% had received opioid prescriptions that posed risk to their health. About 7% met the criteria for receipt of high-risk opioid prescriptions, 3% obtained opioids from three or more pharmacies during a 3-month period, and 4% of spouses who received any opioids received both long-term and high-risk prescriptions. Adverse childhood experiences, physical pain, and lack of social support were associated with increased odds of obtaining high-risk opioid prescriptions. Conclusions: Approximately 48% of military spouses had used Military Health System insurance to fill at least one opioid prescription during the 2-year observation period. The Department of Defense has taken measures to minimize high-risk opioid prescribing, including passing prescribing guidelines in 2017, establishing the controlled drug management analysis reporting tool, establishing a pain management education and training program, and more. These efforts should continue to expand as reducing the numbers of service members and spouses at risk for adverse events may be effective in reducing opioid misuse and improve the overall health and safety of military spouses and thus, the readiness of the U.S. Armed Forces.